Exploring Teachers' Perceptions and Practices in Education for Sustainable Development (ESD) in Public Schools of Karachi - Shakir, Farheen; Naz, Amber; Ahmed, Syeda Mehjabeen (Pakistan Journal of Humanities and Social Sciences, 2024)
The research focuses on the key role of teachers in incorporating SDGs into the curriculum and teaching students to deal with global challenges such as climate change, poverty, and sustainable living. Utilizing a quantitative approach, data were collected from a sample of 100 teachers using a survey method. This research focused on the integration of ESD, the challenges faced by the teachers, and the effect of professional development programs (PDPs) to make the teachers capable of working towards sustainability. The data analysis was done by performing one-sample T-tests to find out the teachers' beliefs and attitudes towards the integration of ESD and Chi-square tests to explore the relationship of the perceived barriers or facilitators and the ESD integration. Correlation analysis showed strong associations between age and ESD understanding being among the key findings. The results showed that teachers have a good grasp of the core ESD concepts and, moreover, they expressed the assurance in the integration of sustainability principles into their teachings. The study demonstrates the key role that teachers play in dynamic the growth of a sustainable development and emphasizes the point that teachers should be given access to the necessary knowledge, skills, and resources so as to create a more sustainable future for the learners and community. Recommendations include ESD to be integrated into the curriculum, professional development programs for teachers, funding provision to facilitate ESD initiatives, encouraging the community to be involved in the process, and advocating for supportive policies from the government. Future research might focus on the long term impact of ESD integration on student achievements, and develop innovative strategies for overcoming the obstacles to the successful implementation of sustainable development programs in public schools.